OPTIMALISASI PEMANFAATAN TERMINAL TIPE C DI KABUPATEN TEGAL - Fatah, Muhamad Nadhorudin; Mudiyono, Rachmat; Niam, Mohammad Faiqun (UNISSULA Semarang, 2023)
Transportation is an important means to support the success of development and to facilitate economic activities in the community. Economic growth in Tegal Regency has resulted in increased mobility, which requires efforts to improve service quality and add effective transportation infrastructure. In order to improve transportation in Tegal Regency, the government has implemented a policy to relocate and build a representative Type C transport terminal with the aim of solving traffic problems in the Central Business District (CBD) area of Tegal Regency. Relocating the Type C transport terminal in Tegal Regency is necessary to improve the effectiveness of terminal relocation. Therefore, a study was conducted on the Optimization of Type C Terminal Relocation Utilization in Tegal Regency (Case Study: Dukuhsalam Village, Slawi District, Tegal Regency) using a quantitative descriptive research method to find out the effectiveness of terminal relocation. The analysis conducted includes technical analysis, economic analysis, traffic analysis, and environmental analysis. Based on the results of the analysis, it was concluded that terminal relocation is considered effective. The technical analysis shows that the infrastructure and facilities of the new terminal are more complete compared to the revitalization of the old terminal. Economic analysis shows that the return on investment for the new terminal can be achieved 2 years faster compared to revitalizing the old terminal. Relocating the new terminal can reduce congestion costs by IDR 1,158,096.00 per day and reduce environmental damage costs by IDR 1,414,088.93. Therefore, optimizing the Type C terminal in Tegal Regency can be achieved by relocating it to a new location.